Analytical Methods INAA and PIXE Applied to Characterization of Airborne Particulate Matter in Bandung, Indonesia - D.D. Lestiani; M. Santoso (PPIKSN-BATAN, 2011)
Urbanization and industrial growth have deteriorated air quality and are major cause to air pollution. Air pollution through fine and ultra-fine particles is a serious threat to human health. The source of air pollution must be known quantitatively by elemental characterization, in order to design the appropriate air quality management. The suitable methods for analysis the airborne particulate matter such as nuclear analytical techniques are hardly needed to solve the air pollution problem. The objectives of this study are to apply the nuclear analytical techniques to airborne particulate samples collected in Bandung, to assess the accuracy and to ensure the reliable of analytical results through the comparison of instrumental neutron activation analysis (INAA) and particles induced X-ray emission (PIXE). Particle samples in the PM2.5 and PM2.5-10 ranges have been collected in Bandung twice a week for 24 hours using a Gent stacked filter unit. The result showed that generally there was a systematic difference between INAA and PIXE results, which the values obtained by PIXE were lower than values determined by INAA. INAA is generally more sensitive and reliable than PIXE for Na, Al, Cl, V, Mn, Fe, Br and I, therefore INAA data are preffered, while PIXE usually gives better precision than INAA for Mg, K, Ca, Ti and Zn. Nevertheless, both techniques provide reliable results and complement to each other. INAA is still a prospective method, while PIXE with the special capabilities is a promising tool that could contribute and complement the lack of NAA in determination of lead, sulphur and silicon. The combination of INAA and PIXE can advantageously be used in air pollution studies to extend the number of important elements measured as key elements in source apportionment. Received: 20 November 2010; Revised: 09 August 2011; Accepted: 15 August 2011